541 Perspectives of older sri lankans on transport-related risks influencing their social participation. (1st September 2016) - Tennakoon, Varuni; Wickramasinghe, Rajitha; Peiris-John, Roshini; Daskon, Lasanthi; Attanayake, Senarath; Bandara, Saman; Ameratunga, Shanthi
Abstract : Background: Perceived risks of road injury can reduce opportunities for social participation and physical activity among older people. These risks are particularly important in low and middle income countries undergoing rapid motorization. This study aimed to explore older peoples' perceptions of opportunities and challenges for social participation, particularly including transport-related risks, in the Moneragala district of Sri Lanka. The Provincial Council of this region has initiated a process to make the district age and disability-friendly. Methods: This qualitative study involved four focus group discussions (8–10 participants in each) with community-dwelling older people aged 60 years and older. The research sought to identify perceived physical and social environmental facilitators and challenges that influenced ease of access to the local and regional destinations that are most important to respondents. Results: Places frequently visited by older people were the hospital, temple, Sunday fair, community hall and bank. The commonest modes of transportation used by respondents included the public bus, walking, and hired three-wheeled vehicles. Participants identified several challenges that increased their exposure to injuries and perceptions of safety including poor road conditions, lack of a disability-friendly transportation system, poor accessibility and negative attitudes of the wider community. Conclusions: The perceptions and experiences reported by older Sri Lankans emphasise the need to develop and implement road designs, infrastructure and age- and disability- friendly transportation systems; public policies that enhance accessibility; and raise public awareness of the needs and aspirations of older people. These efforts would have the potential to promote resilient communities that enable vulnerable communities at risk of social exclusion, particularly older people, to live the lives they value.